فعالية استخدام وسائل الإعلام التعلمية في درس مهارة الإستماع والكلام على التطبيقات السمعية البصرية - Asni Furoidah Furoidah (INAIFAS PRESS, 2019)
The effectiveness of instructional media, especially audio-visual media, is not just channeling messages, but also helps simplify the process of receiving difficult messages so that the communication process is smooth. The students are very happy if in a process of teaching and learning using a variety of creative and innovative media that can cause motivation, especially for use in learning the skills of Istima kalam (listening and speaking). Because of the importance of the use of media in learning Istima skills, the writer is interested in studying the effectiveness of using audio-visual media for mastery of Istima skills in students.